How Swift Is Cry-Mediated Magnetoreception? Conditioning in an American Cockroach Shows Sub-second Response - Slaby, Pavel; Bartos, Premysl; Karas, Jakub; Netusil, Radek; Tomanova, Kateřina; Vacha, Martin (Frontiers in Behavioral Neuroscience, 2018)
Diverse animal species perceive Earth’s magnetism and use their magnetic sense to orientate and navigate. Even non-migrating insects such as fruit flies and cockroaches have been shown to exploit the flavoprotein Cryptochrome (Cry) as a likely magnetic direction sensor; however, the transduction mechanism remains unknown. In order to work as a system to steer insect flight or control locomotion, the magnetic sense must transmit the signal from the receptor cells to the brain at a similar speed to other sensory systems, presumably within hundreds of milliseconds or less. So far, no electrophysiological or behavioural study has tackled the problem of the transduction delay in case of Cry-mediated magnetoreception specifically. Here, using a novel aversive conditioning assay on an American cockroach, we show that magnetic transduction is executed within a sub-second time span. A series of inter-stimulus intervals between conditioned stimuli (magnetic North rotation) and unconditioned aversive stimuli (hot air flow) provides original evidence that Cry-mediated magnetic transduction is sufficiently rapid to mediate insect orientation.